Improving the Methodology of Teaching English to Pedagogy Students through CLIL Technology: The Case of Creative Pedagogy - Saydakhmatova, Mohtobakhon Mukhtoralizoda (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
In recent years, the CLIL (Content and Language Integrated Learning) approach has become one of the most innovative and effective methods in the field of foreign language teaching. It combines content learning with language acquisition, helping students master both simultaneously. The relevance of this research lies in the need to modernize English language teaching methodology in pedagogical education by linking linguistic and professional competencies. Creative Pedagogy serves as an ideal platform for implementing CLIL because it emphasizes imagination, independent thinking, and practical application — key elements for future teachers.